2020
DOI: 10.7150/jca.41828
|View full text |Cite
|
Sign up to set email alerts
|

PLOD2 increases resistance of gastric cancer cells to 5-fluorouracil by upregulating BCRP and inhibiting apoptosis

Abstract: Background: Gastric cancer (GC) is one of the most common cancers, and it is the third most common cause of cancer-related mortality worldwide. Fluorouracil (5-FU)-based chemotherapy is frequently used for the treatment of advanced GC. However, a substantial proportion of patients eventually experience refractory disease due to drug resistance. PLOD2 was reported to increase invasion and migration in several GC cell lines, but the roles of PLOD2 in chemoresistance are still unclear. The present study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…In a variety of tumors, fibrous collagen is considered to provide a channel for cancer cell migration and is mainly modified by PLOD2. For example, PLOD2 can increase the invasiveness and migration of gastric cancer (GC) cells and promote their resistance to 5-fluorouracil by upregulating BCRP and inhibiting apoptosis ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a variety of tumors, fibrous collagen is considered to provide a channel for cancer cell migration and is mainly modified by PLOD2. For example, PLOD2 can increase the invasiveness and migration of gastric cancer (GC) cells and promote their resistance to 5-fluorouracil by upregulating BCRP and inhibiting apoptosis ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PLOD2 may affect cancer progression by modulating collagen cross-linking and maturation ( Kurozumi et al, 2016 ). Wang et al (2020) indicated that PLOD2 can increase the resistance of GC cells to 5-fluorouracil by upregulating BCRP and inhibiting apoptosis. Several studies have indicated that PLOD2 is correlated with poor prognosis of multiple cancers, including sarcoma, GC, lung cancer, renal cell carcinoma, breast cancer, cervical cancer, and bladder cancer ( Miyamoto et al, 2016 ; Du et al, 2017 ; Kiyozumi et al, 2018 ; Chang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the genotype-phenotype correlation of BRKS2 is not fully established, owing to the low amount and relatively clustered distribution of constitutional variations in PLOD2 , the vague structural and functional delineation of the N-terminal of LH2 protein as well as the strong phenotypic variability of BRKS2 (Tham et al, 2018 ; Mumm et al, 2020 ). Furthermore, given the commonality of cell signaling pathways between BRKS2 and multiple types of cancers, the in-depth study of corresponding molecules would benefit scientific and clinical understanding in both fields (Guo et al, 2018 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%